2011
DOI: 10.1016/j.mri.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI using T1ρ and T2 in human osteoarthritic cartilage specimens: correlation with biochemical measurements and histology

Abstract: Purpose-A direct correlation between T 1ρ , T 2 and quantified proteoglycan and collagen contents in human osteoarthritic cartilage has yet to be documented. We aimed to investigate the orientation effect on T 1ρ and T 2 values in human osteoarthritic cartilage; and to quantify the correlation between T 1ρ , T 2 , versus biochemical composition and histology in human osteoarthritic cartilage.Materials and Methods-Thirty-three cartilage specimens were collected from patients who underwent total knee arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
205
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(209 citation statements)
references
References 36 publications
4
205
0
Order By: Relevance
“…Other studies have shown only a moderate correlation with proteoglycan content with no correlation with collagen content [55] nor water content [108]. Additionally, a recent study found that T 1r and GAG content can be correlated in the deeper zones but not in the upper half of cartilage [109].…”
Section: T 1r Mappingmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies have shown only a moderate correlation with proteoglycan content with no correlation with collagen content [55] nor water content [108]. Additionally, a recent study found that T 1r and GAG content can be correlated in the deeper zones but not in the upper half of cartilage [109].…”
Section: T 1r Mappingmentioning
confidence: 92%
“…Additionally, studies have shown that T 1r tends to reflect depth-dependent trends in T 2 [33], with the highest T 1r values at the superficial tangential zone and decreasing values reaching a minimum at either the middle zone [28,51] or the deep zone [33,110]. Although the exact relationship of T 1r to proteoglycan or other biochemical content in articular cartilage remains unclear [55,107], T 1r mapping is gaining momentum as a viable technique for imaging of cartilage biochemistry.…”
Section: T 1r Mappingmentioning
confidence: 99%
“…While T 2 relaxation times is primarily affected by hydration and collagen structure due to dipolar interactions (5), the spin-lock techniques used in T 1ρ reduce dipolar interactions (6). Chemical exchange on proteoglycan and water protons was suggested to contribute to T 1ρ in cartilage, although T 1ρ changes in cartilage may be affected by hydration and collagen structure as well (7). T 1ρ quantification was adopted in previous study to detect early signs of OA (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative MRI techniques, however, including T 1q relaxation time mapping, enable the assessment of cartilage composition noninvasively and are useful to visualize the loss of collagen matrix that occurs early in the OA disease process [1,33,44,45]. An increase in T 1q relaxation times indicates loss of proteoglycans and possibly a concomitant increase in hydration [1,33,34,38]. T 1q relaxation times have been shown to detect early knee cartilage degeneration in multiple studies [33,49,53,55].…”
Section: Introductionmentioning
confidence: 99%